2018
DOI: 10.1002/adsc.201701603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Application and Kinetic Studies of Chiral Phosphite‐Oxazoline Palladium Complexes as Active and Selective Catalysts in Intermolecular Heck Reactions

Abstract: This study identifies new phosphite-oxazoline ligands that have been successfully applied in the palladiumcatalyzed intermolecular asymmetric Heck reaction. The design of the new phosphite-oxazoline ligands derives from a previous successful generation of phosphine-oxazoline ligands, by replacing the phosphine group with several πacceptor biaryl phosphite moieties. With these simple modifications, the new phosphite-based ligands, unlike previous phosphine-oxazoline, not only present a modular design with numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…[ 7 ] Chiral phosphite‐oxazoline ligand L3 also showed excellent asymmetric induction in the arylation of such heterocyclic olefins, leading to excellent enantioselectivities and high conversions. [ 10 ] As shown in Scheme 17,…”
Section: Palladium‐catalyzed Intermolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] Chiral phosphite‐oxazoline ligand L3 also showed excellent asymmetric induction in the arylation of such heterocyclic olefins, leading to excellent enantioselectivities and high conversions. [ 10 ] As shown in Scheme 17,…”
Section: Palladium‐catalyzed Intermolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…In 2018, Pàmies, Leeuwen, and Diéguez synthesized a range of phosphite‐oxazoline ligands derived from 2‐hydroxyphenylacetonitrile, among which ligand L3 could lead to high conversions (up to 99%) and excellent enantioselectivities (up to 96% ee) in the Heck coupling of cyclopentene with aryl triflates (Scheme 5). [ 10 ]…”
Section: Palladium‐catalyzed Intermolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…Therefore, efforts have recently been made to design novel anticancer drugs based on palladium compounds . In addition, these compounds have attracted renewed interest due to their wide applications in catalytic processes, construction of chemical sensors, and antibacterial and cytotoxicity usage …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts have recently been made to design novel anticancer drugs based on palladium compounds. [20][21][22] In addition, these compounds have attracted renewed interest due to their wide applications in catalytic processes, [23][24][25] construction of chemical sensors, [26] and antibacterial and cytotoxicity usage. [27] Based on the literature, a great number of recent publications have focused on finding suitable alternatives for hazardous solvents, and ionic liquids (ILs) have emerged as appropriate candidates for use in sustainable chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands gave up to 96% ee by their application in allylic substitution with dimethyl malonate as nucleophile [ 13 14 ]. The design of new PHOX ligands is still subject to current research and the synthesis of a lot of different PHOX ligands have been reported during the last years [ 15 18 ]. Kunz reported the preparation of a carbohydrate based PHOX ligand 2 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%